Relationship between serum zinc levels and febrile seizures: a hospital based case control study - Ahmed, Shakeel; Kailas, Lalitha; Nair, Rekha S. (International Journal of Contemporary Pediatrics, 2025)
Background: Febrile seizures are common in children and are influenced by multiple factors, including micronutrient levels. Zinc is believed to play a crucial role in neuronal excitability and immune modulation. To compare serum zinc levels in children with febrile seizures and those with febrile illness without seizures and to examine associations between zinc levels and variables such as age, gender, seizure type, recurrence and clinical presentation. Methods: A prospective case-control study was conducted at Sree Gokulam Medical College, Kerala, from December 2022 to June 2024. The study included 158 children aged 6 to 72 months: 79 with febrile seizures (cases) and 79 with febrile illness without seizures (controls), matched for age, sex and clinical presentation. Serum zinc levels were measured using colorimetry. Results: Mean serum zinc levels were significantly lower in the case group (81.1 µg/dl) compared to the control group (142 µg/dl), with a mean difference of 61.3 µg/dl (p<0.01). Hypozincemia (serum zinc<65 µg/dl) was found in 48% of cases versus 6% of controls. No significant associations were observed between serum zinc levels and age, gender, seizure type, recurrence or clinical presentation. Conclusions: Children with febrile seizures had significantly lower serum zinc levels compared to febrile controls. The higher prevalence of hypozincemia in the case group suggests zinc deficiency may contribute to febrile seizure risk, highlighting the need for further research on zinc’s role in seizure prevention.